2020
DOI: 10.1002/jso.26173
|View full text |Cite
|
Sign up to set email alerts
|

What are the predictors of emergency department utilization and readmission following extremity bone sarcoma resection?

Abstract: Introduction: Treatment for bone sarcomas are large undertakings. Emergency department (ED) visits and unplanned hospital readmissions are a potential target for cost containment. The purpose of this study was to evaluate the risk factors for ED visits and unplanned readmissions following extremity bone sarcoma surgery. Methods: Data from Optum Labs Data Warehouse, a national administrative claims database, was analyzed to identify patients with extremity bone sarcomas from 2006 to 2017. Multivariable logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…The rationale behind this appears to relate to the fact that, for surgical oncologic episodes of care, costs tend to be much higher than most other elective surgeries 13,23 . Despite this focus on readmission and value across surgical oncology as a whole, data to guide Orthopaedic oncologists towards evidence based and value driven care of sarcomas and other oncologic diagnoses remains limited 16–18 . One study by Wellings et al 17 utilized a claims database to investigate the predictors of readmission following extremity bone sarcoma resection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The rationale behind this appears to relate to the fact that, for surgical oncologic episodes of care, costs tend to be much higher than most other elective surgeries 13,23 . Despite this focus on readmission and value across surgical oncology as a whole, data to guide Orthopaedic oncologists towards evidence based and value driven care of sarcomas and other oncologic diagnoses remains limited 16–18 . One study by Wellings et al 17 utilized a claims database to investigate the predictors of readmission following extremity bone sarcoma resection.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this focus on readmission and value across surgical oncology as a whole, data to guide Orthopaedic oncologists towards evidence based and value driven care of sarcomas and other oncologic diagnoses remains limited 16–18 . One study by Wellings et al 17 utilized a claims database to investigate the predictors of readmission following extremity bone sarcoma resection. They found that the readmission rate was 18.0% within 30 days, findings that align with the 19.4% readmission rate in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations